2020
DOI: 10.1002/admt.202000073
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Strain‐Insensitive, Hyperelastic Temperature‐Sensing Fiber with Compressed Micro‐Wrinkles for Integrated Textronics

Abstract: Fiber‐shaped sensors are useful for the simple fabrication of textile‐based electronics, which have excellent wearability and conformal adaptability for ubiquitous healthcare systems. In the case of temperature monitoring using highly deformable textronics for diagnostics, the device operation can be hindered by strain‐induced interferences when various movements are performed. An intrinsic strain‐insensitive fiber‐type temperature sensor with compressed micro‐wrinkles is demonstrated. The fiber sensor exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
0
49
0
Order By: Relevance
“…Copyright Royal Society of Chemistry 2019; (c) Relative changes in the electrical resistance, indicating excellent strain-insensitivity under various tensile stresses induced by lateral strains. Reprinted with permission from ref . Copyright John Wiley and Sons 2020; (d) Photographs showing the frozen hydrogel and the Gly-organo-hydrogel withstood 180° twist deformation after storing at −18 °C for 24 h; Gly-organo-hydrogel can be stretched to 660% strain after cooling at −18 °C for 24 h; Temperature response with various strains and sensitivity of Gly-organo-hydrogels.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright Royal Society of Chemistry 2019; (c) Relative changes in the electrical resistance, indicating excellent strain-insensitivity under various tensile stresses induced by lateral strains. Reprinted with permission from ref . Copyright John Wiley and Sons 2020; (d) Photographs showing the frozen hydrogel and the Gly-organo-hydrogel withstood 180° twist deformation after storing at −18 °C for 24 h; Gly-organo-hydrogel can be stretched to 660% strain after cooling at −18 °C for 24 h; Temperature response with various strains and sensitivity of Gly-organo-hydrogels.…”
Section: Applicationsmentioning
confidence: 99%
“…Fiber-based wearable temperature sensors, which can be integrated into multifunctional textiles, have also been studied as one of the strain-suppression strategies. ,, For instance, Nae-Eung Lee and co-workers proposed a free-standing reduced graphene oxide/polyurethane composite fiber . The author engineered this fiber into a serpentine structure on a PDMS substrate or a stretchable fabric to suppress the external strain.…”
Section: Applicationsmentioning
confidence: 99%
“…The developed composite fibers can be used both as electrically conductive paths in textronics and as tensile sensors due to the piezoresistive phenomenon. According to the literature, there are many methods to integrate conductive fibers into the fabric, but two main ways can be determined: sewing [36][37][38] or deposition directly into the fabric [39][40][41][42][43]. Both methods of producing conductive paths on the fabrics were tested during our research.…”
Section: Applicationsmentioning
confidence: 99%
“…Regardless of material selection, the electrical contact between conductive fillers determines the conductivity; during stretch, conductive fillers may separate from each other, leading to the deterioration of conductivity (16). As most conductive media are rigid with unchangeable conductivity, a generally adopted strategy to design strain-insensitive fiber conductors is to induce solely the geometric distortion of conductive path via a prestrain buckling process or simply shaping the fiber in wavy or helical structures (7,(17)(18)(19)(20)(21)(22)(23)(24). For example, Liu et al (7) reported superelastic conducting sheathcore fibers with a hierarchically buckled sheath prepared by wrapping carbon nanotube sheets on prestretched rubber fiber cores, which enables a resistance change of less than 5% for a 1000% stretch.…”
Section: Introductionmentioning
confidence: 99%